2014
DOI: 10.1371/journal.pone.0097233
|View full text |Cite
|
Sign up to set email alerts
|

ANP32B Is a Nuclear Target of Henipavirus M Proteins

Abstract: Membrane envelopment and budding of negative strand RNA viruses (NSVs) is mainly driven by viral matrix proteins (M). In addition, several M proteins are also known to be involved in host cell manipulation. Knowledge about the cellular targets and detailed molecular mechanisms, however, is poor for many M proteins. For instance, Nipah Virus (NiV) M protein trafficking through the nucleus is essential for virus release, but nuclear targets of NiV M remain unknown. To identify cellular interactors of henipavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…Supporting the idea of a critical role in virus particle formation and budding, NiV M protein forms virus-like particles (VLPs) when expressed on its own (12,13), and it drives apical assembly and budding of NiV virions in polarized epithelial cells (14). Trafficking of NiV M is a complex process involving transit through the nucleus (15)(16)(17)(18), despite replication occurring exclusively in the cytoplasm. When NiV M protein nuclear localization or export signals are interrupted, or if the endosomal sorting complexes required for transport (ESCRT) pathway-interacting late domains are disrupted, NiV M proteins lose their ability to accumulate at the plasma membrane and no longer generate virus-like particles (12,17,19).…”
mentioning
confidence: 99%
“…Supporting the idea of a critical role in virus particle formation and budding, NiV M protein forms virus-like particles (VLPs) when expressed on its own (12,13), and it drives apical assembly and budding of NiV virions in polarized epithelial cells (14). Trafficking of NiV M is a complex process involving transit through the nucleus (15)(16)(17)(18), despite replication occurring exclusively in the cytoplasm. When NiV M protein nuclear localization or export signals are interrupted, or if the endosomal sorting complexes required for transport (ESCRT) pathway-interacting late domains are disrupted, NiV M proteins lose their ability to accumulate at the plasma membrane and no longer generate virus-like particles (12,17,19).…”
mentioning
confidence: 99%
“…Alanine mutagenesis of key leucine residues in corresponding sequences in the M proteins of HeV, SeV and MuV also increased their nuclear accumulation (Pentecost et al, 2015), indicative of conservation of the NES in multiple paramyxoviruses. As HeV M export is inhibited by LMB, it appears that this NES is CRM1 dependent (Bauer et al, 2014). Equivalent mutations in NDV M and MeV M, however, did not cause nuclear accumulation (Pentecost et al, 2015), suggestive of divergence in the NESs used by these proteins.…”
Section: Mevmentioning
confidence: 95%
“…Disruption of either of the two putative classical leucine-rich NES sequences in NiV-M increased nuclear localization of M, but only the N-terminal NES-mediated nuclear export when fused to a heterologous protein [33]. As expected for a protein bearing a leucine-rich NES, nuclear export of M is sensitive to inhibition with leptomycin B (LMB) [66], indicating transport requires chromosome region maintenance 1 (Crm1, XPO1), one of the seven karyo-pherin-β superfamily nuclear export proteins (XPO1-7) [67,68]. …”
Section: Niv-m Nuclear Exportmentioning
confidence: 99%
“…Interestingly, a proteomics-based interaction study identified acidic leucine-rich nuclear phosphoprotein 32 member B (ANP32B), a Crm1 transport adaptor for mRNA [69], as a HNV matrix (HNV-M)-interacting protein [66]. Overexpression of ANP32B resulted in nuclear retention of both NiV and HeV-M, suggesting a possible role in M protein trafficking [66].…”
Section: Niv-m Nuclear Exportmentioning
confidence: 99%